Pengaruh Latihan Ladder Drill dan Lari Zig-Zag Terhadap Kemampuan Dribbling dalam Permainan Sepak Bola di Club Persitta Fc Talang Taling - Gilang Kurniawan; Putri Cicilia Kristin; Endie Riyoko (Departement of Mathematics Education, 2023)
The problem in this research is the lack of ability of Persitta Fc Talang Taling athletes to do dribbling. The purpose of this study was to determine the effect of ladder drill and zig-zag running exercises on the dribbling abilities of football athletes at the Persitta Fc club. This research method is a quasi-experimental, two group pretest-posttest design, namely the division of the experimental group is divided into two groups using ordinal pairing using the A-B-B-A pattern, as well as the data collection technique using tests. The instrument used is a dribbling ability test. The subjects in this study were 20 Persitta Fc club athletes, taking samples by census or total sampling. Data analysis techniques used hypothesis testing with t-test analysis. The results obtained from the experimental group 1 t-count value = 5.756 ≥ t-table = 1.833 and the results of the experimental group 2 study t-count value = 6.509 ≥ t-table = 1.833 There is a difference from the two exercises to improving the dribbling ability of Persitta Fc athletes. And to find out which of the two exercises has the most effect, the results of the pretest and posttest average scores in the experimental group 1 are 28.40 and 24.20. While the average pretest and posttest scores in the experimental group 2 were 28.48 and 24.32. Thus there was an increase of 4.20 in the experimental group 1 while the increase in the experimental group 2 was 4.16. The results of this study indicate that ladder drill exercises have a better effect on improving dribbling abilities than zig-zag running exercises in dribbling skills.